Influence of arterial mechanical properties on carotid blood flow: Comparison of CFD and FSI studies. (September 2019) - Lopes, D.; Puga, H.; Teixeira, J.C.; Teixeira, S.F.
Highlights: This work relates atherosclerosis with increased arterial stiffness of a patient-specific carotid geometry. Compared with elastic wall studies (FSI), the rigid wall study (CFD) overestimated the values of velocity and wall shear stress profiles. Increased arterial stiffness doesn't influence the distribution of flow rate through the outlet arteries. Increased arterial stiffness induces smaller displacements of the artery and consequently elevated flow velocity. Abstract: Carotid artery blood flow is studied to compare models with rigid and elastic walls. Considering a patient-specific geometry and transient boundary conditions. In the case of rigid walls, only the fluid (blood) behavior is considered, in a typical Computational Fluid Dynamics study. With the elastic walls, the reciprocal influence of both fluid and solid (blood and artery) are taken into account, constituting a Fluid-Structure Interaction study. Furthermore, the study of the influence of mechanical properties of the artery, which become stiffer with the progression of atherosclerosis, on blood flow is also presented, an innovative approach relative to the work done in this field. Results show that the carotid sinus is the preferential zone to develop atherosclerosis, given its low values of Time-Averaged Wall Shear Stress. Additionally, it is fundamental to consider the arterial wall as elastic bodies, given that the rigid model overestimates the flow velocity and Wall Shear Stress. On the different mechanical properties of the vessel, its influence is minimal in the Time-Averaged Wall Shear Stress profiles. However, given the results of the displacement and velocity profiles, their inclusion in blood flow simulations in stenosed arteries should be considered. Graphic abstract: Image, graphical abstract